2017
DOI: 10.1038/nri.2017.10
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils as protagonists and targets in chronic inflammation

Abstract: Traditionally, neutrophils have been acknowledged to be the first immune cells that are recruited to an inflamed tissue and have mainly been considered in the context of acute inflammation. By contrast, their importance during chronic inflammation has been studied in less depth. This Review aims to summarize our current understanding of the roles of neutrophils in chronic inflammation, with a focus on how they communicate with other immune and non-immune cells within tissues. We also scrutinize the roles of ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
371
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 451 publications
(401 citation statements)
references
References 151 publications
5
371
0
3
Order By: Relevance
“…This suggests a systemic anti-inflammatory effect of RS. Reduced inflammation could explain a restoration in bone marrow physiology reflected by normalization of blood disorders (anemia and leukocytosis), bone marrow cellular repletion, and restored granulocyte-monocyte and megakaryocyte-erythrocyte progenitors populations (Figures S6D-S6F) (Soehnlein et al, 2017; Trompette et al, 2018; Ueda et al, 2005). Importantly, RS also significantly reduced renal immune infiltration and glomerulonephritis as well as proteinuria levels in TLR7.1 Tg mice (Figures 6G-6I).…”
Section: Resultsmentioning
confidence: 99%
“…This suggests a systemic anti-inflammatory effect of RS. Reduced inflammation could explain a restoration in bone marrow physiology reflected by normalization of blood disorders (anemia and leukocytosis), bone marrow cellular repletion, and restored granulocyte-monocyte and megakaryocyte-erythrocyte progenitors populations (Figures S6D-S6F) (Soehnlein et al, 2017; Trompette et al, 2018; Ueda et al, 2005). Importantly, RS also significantly reduced renal immune infiltration and glomerulonephritis as well as proteinuria levels in TLR7.1 Tg mice (Figures 6G-6I).…”
Section: Resultsmentioning
confidence: 99%
“…[60] Thus, inhibition of neutrophil trafficking to the inflamed tissue is an essential process for the resolution of inflammation. Both Ac2-26 and its nanotherapies effectively inhibited macrophage apoptosis as well as reduced ROS generation and inflammatory response in stimulated macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…[60] Thus, inhibition of neutrophil trafficking to the inflamed tissue is an essential process for the resolution of inflammation. [60] We found that AON exerted its anti-inflammatory and proresolving actions through FPR2, and the antiapoptotic activity in macrophages was largely attributed to FPR1 activation. [62,63] In addition, macrophage phagocytic clearance of apoptotic neutrophils plays an important role in resolving inflammation, since this process can prevent excessive neutrophil activation and the exposure of tissues to noxious intracellular contents of neutrophils or neutrophil extracellular traps.…”
Section: Discussionmentioning
confidence: 99%
“…Impaired neutrophil chemotaxis, due to genetic defects [2] or to pathological conditions such as major burn [3] or drug treatment such as chemotherapy [4], weakens the host defense against pathogens and may further lead to severe infections. On the opposite side, excessive activation and recruitment of neutrophils in an uncontrolled manner may lead to chronic inflammation [5] and organ failure [6]. Thus, understanding neutrophil chemotaxis in homeostasis and pathology can provide important insights in clinical diagnosis, treatment, and prognosis of diseases.…”
Section: Introductionmentioning
confidence: 99%